BIRTH OF THE NUCLEUS  1964 - Durrani, S. A. (The Nucleus, 2020)
The article describes how Dr I H Usmani, the-then Chairman of the Pakistan Atomic Energy Commission (PAEC) threw down the gauntlet, in mid-1963, to the author of this paper – then a young and recently-recruited Director of the Atomic Energy Centre, Lahore – inviting him to be the Founder-Editor of the quarterly journal of the PAEC. The author took up the challenge – and The Nucleus was born in March 1964. The author presents an overview of the philosophy, the overall structure / coverage of topics, the artistic get-up, as well as the composition of the multidisciplinary first Editorial Board of the journal. Reference is also made to the contents of some of the early issues of The Nucleus, edited by the author. The article ends with a description of the evolution to the present-day – more technical – nature of the journal.